SAAMCO, The Scope of the Duty and Liability for Consequences - Hegan, Nick (Victoria University of Wellington Law Review, 2007)
The House of Lords’ 1996 decision in South Australia Asset Management Corp v York Montague Ltd limiting liability in certain cases of negligent misstatement has been controversial. More recent pronouncements, both judicial and extra-judicial, suggest something of a change in the way judges are analysing the scope of liability for wrongs. This article examines how the SAAMCO decision fits into this new rubric, and whether its policy basis can be better elucidated under it.